Dinamika bazovych fiziceskich kacestv kvalificirovannych tchekvondistov v godicnom cikle podgotovk - Kashkarov, V. A.; Vishnyakov, A. V.; Frolova, T. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Physical training is the basis for technical and tactical, psychological and competitive training in martial arts. The study was designed to investigate the dynamics of physical training indexes of qualified athletes. Based on the practice of competitive activity, a system of training is built. The busy calendar of qualified Taekvondo competitions determines the means and methods used to maintain a high level of physical fitness during the season. The study presents the dynamics of basic indicators of physical fitness, which is maintained at a sufficient level due to proper planning at the basic stages of macrocycles.